Analisis Dampak Revitalisasi Pasar Senaken terhadap Pedagang dan Pengunjung Berdasarkan Aspek-Aspek Revitalisasi - Fadhilah, Atikah Salwa; Adhar, Khairunnisa (COMPACT: Spatial Development Journal, 2025)
This study aims to analyze the impact of the revitalization of Senaken Market on traders and visitors based on aspects of revitalization, including physical, management, economic, and social aspects. The revitalization of Senaken Market, which has been ongoing since 2022, is a response to various physical problems in the market, such as damage to market buildings due to fire, squalor, and disrupted circulation within the market. This study is a mixed-method research using a quantitative survey method through the distribution of questionnaires to 100 visitors and 94 vendors. Analysis was conducted using the Likert scale scoring method to measure perceptions of the revitalization's impact, followed by a descriptive interpretation of the scoring results. The results of the study indicate that the impact of revitalization is generally perceived as positive, particularly in terms of physical aspects and some social aspects. However, in terms of economic and management aspects, several challenges remain, such as the uneven increase in vendors' income and the suboptimal empowerment of vendors by market managers.